A MARKETING MANAGEMENT MENTORING : STRENGTHENED MANAGEMENT FOR SURVIVAL MICRO, SMALL AND MEDIUM BUSINESS DURING PANDEMIC COVID 19 - utami budi (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
The Covid-19 pandemic has had a serious impact on the economy. Economic activity has been hampered due to widespread health issues. As a result, many aspects of life are affected, especially in micro, small and medium enterprises (MSMEs). Sales fell significantly due to the declining purchasing power of the people. This is also experienced by the WanQi Factory micro, small and medium enterprises (MSMEs). This home industry (MSME) produces and markets bags and accessories. During the pandemic covid 19, WanQi Factory experienced a very significant decrease in sales. If this continues continuously, it is certain that WanQi Factory's home industry (MSMEs) will close its business or experience a wall. Managerial action is therefore required to address the issue. The method of implementation of this activity is to observe, identify problems and mentor problem solutions by monitoring and mentoring management. The solutions offered do digital marketing, branding and expansion of the sales area